La imagen de Aragón en los libros de texto de Educación Primaria - Climent López, E.; García Pascual, E.; Ruiz Budría, E. (Geographicalia, 2016)
This paper is aimed at revealing the image of Aragon (Spain) that textbooks of primary education communicate to children. The conclusions we reach are that all textbooks keep to the classical academic pattern, distinguishing ones with a merely descriptive approach from others with a pre-scientific one. Graphics are half the printed area and serves the function of explaining the written text, but the maps are of low quality. All textbooks hold an important number of factual and conceptual errors, and show Aragon like a rural and backward region producing foods and raw materials, which is a wrong stereotype.